The Development of Physiological Growth Model of Beef Cattle in Semi Arid Environment to Meet Beef Demands for Tourism Sectors in East Nusa Tenggara - Kapa, Maximilian M. J. (Graduate School, Universitas Brawijaya, 2015)
This research was conducted at Raknamo and Tuatuka Villages, Amabi Oefeto Sub-District, Kupang Regency from September until November 2013. The aim of the research was to (1) build a growth model of beef cattle under extensive management system, and (2) formulate an adaptive model to estimate body weight of local beef cattle that will provide more accurate guessing and also give more benefit to farmer. Results of the research found that (1) beef cattle farming is viewed as an economic activity that uses of resources with low opportunity costs such as family labours and marginal land, (2) The model built showed a positive and very strongh relationship between body weight and girth for both male and female with determinant coefficients of 0.94 and 0.96 respectivelly. It means that body weight variable can be explained well by girth variable. The same condition applied to the relationship between body weight and age for male and female. Where the relationship between the two variables was also positive and and strong enough with determinant coefficients of 0.78 and 0.86 respectively.Keywords: Model, beef cattle, girth, weight, age